2007
DOI: 10.1093/bioinformatics/btm100
|View full text |Cite
|
Sign up to set email alerts
|

iPTREE-STAB: interpretable decision tree based method for predicting protein stability changes upon mutations

Abstract: Dataset and other details are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 13 publications
0
94
0
Order By: Relevance
“…These programs predict features such as the secondary structure, transmembrane regions, and the relative solvent accessibilities of the amino acids based on the amino acid sequence of the given protein. Protein stability was examined using the I-Mutant-3 (33) and MuPro (34) programs, also implemented in PON-P, and an additional program called iPTREE-STAB (35).…”
Section: In Silico Pathogenicity Predictionmentioning
confidence: 99%
“…These programs predict features such as the secondary structure, transmembrane regions, and the relative solvent accessibilities of the amino acids based on the amino acid sequence of the given protein. Protein stability was examined using the I-Mutant-3 (33) and MuPro (34) programs, also implemented in PON-P, and an additional program called iPTREE-STAB (35).…”
Section: In Silico Pathogenicity Predictionmentioning
confidence: 99%
“…. This kind of low-level rule-with conditions referring to specific amino acids in specific positionswas also discovered by Huang et al [27], with the difference that in this case, the rules predict protein stability changes upon mutations. Although the rules discovered in the previous two works do not give as much insight about the data as rules having higher level attributes, they were still considered interpretable by the authors, and they were found to be useful to guide "wetlab" experiments because the explicit sequence features that caused the prediction to be made are identified, and therefore, a specific mutation can be made to validate the prediction.…”
Section: Examples Of Discovered Knowledge Represented By Comprehensibmentioning
confidence: 67%
“…The 4-fold and 20-fold cross-validation tests yielded the accuracy of 81.4% and 82.1% for discriminating the stability of protein mutants. The sensitivity and specificity are 75.3% and 84.5%, respectively [42]. Further, our method could predict the stability of protein mutants with the correlation coefficient of 0.70.…”
Section: Prediction Of Protein Stabilitymentioning
confidence: 80%